2016
DOI: 10.1007/s12011-016-0903-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic and Acute Zinc Supplementation on Myocardial Ischemia-Reperfusion Injury in Rats

Abstract: The present study aims to explore the effects of chronic and acute zinc sulfate supplementation on myocardial ischemia-reperfusion injury in rats. The study registered 50 adult male rats which were divided into five groups in equal numbers as follows: group 1, normal control; group 2, sham; group 3, myocardial ischemia reperfusion (My/IR): the group which was fed on a normal diet and in which myocardial I/R was induced; group 4, myocardial ischemia reperfusion + chronic zinc: (5 mg/kg i.p. zinc sulfate for 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Cardiac and plasma Zn levels are severely depleted in patients post-myocardial infarction, the extent of depletion correlating with myocardial infarction outcome (8) and with the levels of enzyme markers (lactate dehydrogenase and creatine kinase) of the extent of myocardial injury and the severity of arrhythmia (9) , leading to the proposal that Zn supplementation given at the time of reperfusion may represent a cardioprotective approach. Indeed, studies have shown that administration of Zn pyrithione at the time of reperfusion in isolated hearts can ameliorate reperfusioninduced injury via the reperfusion injury salvage kinase pathway (10) , improve post-reperfusion contractile recovery and reduce reperfusion-induced ventricular fibrillation (VF) (11) and, in hyperlipidaemic hearts, restore the infarct reducing effect of preconditioning (12) , while chronic Zn supplementation before I/R reduces infarct size and increases cardiac glutathione (GSH) content (13) . Conversely, studies looking at acute Zn depletion, using the Zn chelator TPEN (N,N,N′,N′-tetrakis(2-pyridinylmethyl)-1,2-ethanediamine), demonstrate a worsening of infarct size (reviewed in Lee et al (7) ) but reduced arrhythmia severity (14,15) .…”
mentioning
confidence: 99%
“…Cardiac and plasma Zn levels are severely depleted in patients post-myocardial infarction, the extent of depletion correlating with myocardial infarction outcome (8) and with the levels of enzyme markers (lactate dehydrogenase and creatine kinase) of the extent of myocardial injury and the severity of arrhythmia (9) , leading to the proposal that Zn supplementation given at the time of reperfusion may represent a cardioprotective approach. Indeed, studies have shown that administration of Zn pyrithione at the time of reperfusion in isolated hearts can ameliorate reperfusioninduced injury via the reperfusion injury salvage kinase pathway (10) , improve post-reperfusion contractile recovery and reduce reperfusion-induced ventricular fibrillation (VF) (11) and, in hyperlipidaemic hearts, restore the infarct reducing effect of preconditioning (12) , while chronic Zn supplementation before I/R reduces infarct size and increases cardiac glutathione (GSH) content (13) . Conversely, studies looking at acute Zn depletion, using the Zn chelator TPEN (N,N,N′,N′-tetrakis(2-pyridinylmethyl)-1,2-ethanediamine), demonstrate a worsening of infarct size (reviewed in Lee et al (7) ) but reduced arrhythmia severity (14,15) .…”
mentioning
confidence: 99%
“…After 30 minutes of ischemia, the clamp was opened and the silk passed through the tube was loosened to restore blood supply. These durations of I/R were already successfully used in the same experimental model 14–16 . In the PostC group, the artery was reperfused for 10 seconds following 30‐minute ischemia and then re‐occluded for 10 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…These durations of I/R were already successfully used in the same experimental model. [14][15][16] In the PostC group, the artery was reperfused for 10 seconds following 30-minute ischemia and then re-occluded for 10 seconds. This procedure was repeated three times.…”
Section: I/r Proceduresmentioning
confidence: 99%
“…RNA sequencing and preservation techniques have been detailed elsewhere. 55 Briefly, tissue samples were preserved in RNAlater ® (Ambion, Life Technologies, USA) immediately after collection and sequenced in batches at a later time-point on the Illumina HiSeq 2000 (Illumina, San Diego, CA). Paired-end reads 50, 90, or 100 base pairs long were generated, producing ~134 million reads per sample.…”
Section: Rna Sequencing Alignment and Annotationmentioning
confidence: 99%